Participatory development of incentives to coexist with jaguars and pumas. Issue 4 (13th March 2018) - Amit, Ronit; Jacobson, Susan K.
Abstract: Reducing costs and increasing benefits for rural communities coexisting with large carnivores is necessary for conservation of jaguar ( Panthera onca ) and puma ( Puma concolor ). To design acceptable incentives, stakeholders must be involved in the process. We conducted an innovative, structured, group communication process based on a Delphi technique as a template for identifying potential incentives. Community workshops with 133 members of 7 communities and surveys with 25 multidisciplinary experts from government, nongovernmental organizations, and academia provided iterative data to design a plan of incentives through 4 rounds of discussion. The final product integrated 862 ideas into 6 types of incentives: organization of communities, mechanisms for improved dialogue, citizen technical assistance, green labeling for community products, payment for the ecosystem service of biodiversity, and an assessment of financial alternatives. We used quantitative and qualitative techniques to indicate support for decisions about the design of incentives, which reduced researcher subjectivity. The diverse incentives developed and the cooperation from multiple stakeholders resulted in an incentive plan that integrated issues of governance, equity, and social norms. Abstract : Article impact statement : A structured communication process involving experts and communities enables development of a conservation‐incentive program for big cats.